Upaya Meningkatkan Kedisiplinan Siswa dalam Menaati Tata Tertib Melalui Layanan Penguasaan Konten dengan Teknik Modelling pada Siswa Kelas VII A SMP Negeri 19 Kota Jambi Tahun Ajaran 2015/2016 - Arnita Liana (Jurnal Ilmiah Dikdaya, 2019)
Discipline is one of life skills that is very important and needs to be owned by everyone in order to achieve success in life, not only success in learning but also success in living in a community. Discipline adheres to the order includes three aspects, namely: understanding of the applicable regulations, good mental attitude and sincerity in obeying the rules. The phenomenon in the field shows the disciplinary conditions of class VII A SMP Negeri 19 Kota Jambid in these three aspects are still low. The problem to be examined in this study is to know the description of discipline of VII A grade students in obeying the rules before and after being given content mastery services with modeling techniques. This type of research is experimental research. The population of this study was all students of class VII SMP Negeri 19 Kota Jambi. The sampling technique used was Cluster Random Sampling and class VII A which became the study sample with the number of respondents 32 students. The method of data collection in this study used a disciplinary scale instrument of 63 items. The instrument has been tested for use in research. The method of data analysis uses descriptive percentages and t-tests. The results of the study obtained, the level of discipline of students before getting content mastery services belong to the medium category with a percentage of 66.6% after getting mastery of content increased to 77.6% in the high category. Thus an increase of 11%. From the calculation of the t-test obtained t count = 10.67> t table = 2.04. These results indicate that content mastery services with modeling techniques can improve student discipline.